Contact lens holographic projection display based on curved volume-holographic optical element - Jin Su Lee (ETRI Journal)
Wearable devices for augmented reality (AR) have gained considerable atten-tion but research on contact lenses remains scarce. This study introduces an AR display that utilizes a contact lens integrated with a holographic projection display and a curved volume-holographic optical element. We designed a holo-graphic projection display with a total FoV 15°(supported FoV 10°) and a 6.9 mm × 3.9 mm eyebox, respectively. The computer-generated hologram was optimized to null quality degradation caused by pupil constraints and asymmetric diffraction efficiency distribution. The diffraction efficiency of the holographic optical element used in the contact lens was calculated to provide insights into the anticipated optical performance and identify issues associated with the proposed system. Excellent performance with a maximum diffraction efficiency of 95% is demonstrated under Bragg conditions. However, a substan-tial drop in efficiency is observed at angular deviations 4°. Conversely, the wavelength deviations had a negligible impact on diffraction efficiency. Finally, the proposed contact lens holographic display was optically recon-structed, confirming its potential as a next-generation wearable display technology.